EFFECT OF EMOTIONAL INTELLIGENCE ON SALESPERSON’S EMPLOYEE ENGAGEMENT AND INTENTION TO QUIT: AN EMPIRICAL STUDY - RUPALI SHEKHAR KHANOLKAR (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, ECONOMICS & MANAGEMENT, 2013)
Present paper is aimed at examining relationship between emotional intelligence, employee engagement and intention to quit in field sales representatives in Indian Pharmaceutical Industry. Specifically, this paper argues that Emotional intelligence may be an important determinant of employee engagement and in turn intention to quit among pharmaceutical sales employees. Data was collected from one hundred and sixty field sales employees from pharmaceutical industry in India. The analysis of data showed that there is a high positive correlation between overall scores of emotional intelligence and employee engagement. (Pearson coefficient r=.32) .Employee engagement had a high negative correlation with Intention to quit. (Pearson coefficient r=- .4).There was no significant direct relation found between emotional intelligence and intention to quit. The first two findings support previous study of relationship between Emotional Intelligence, Employee Engagement and Intention to quit .The finding on relationship between emotional intelligence and intention to quit gives direction for further research in that area. It can be concluded from the research that the employer will have to focus on increasing emotional intelligence of employees to have high levels of employee engagement which will lower employee turnover rates.